THE TRANSFORMATION OF R.A. KOSASIH'S MAHABHARATA WAYANG COMICS DESIGN: COMPARISON OF THE 1955 VERSION WITH THE 1975 VERSION - Gunawan, Iwan (International Review of Humanities Studies, 2020)
Mahabharata was an epic Hindu story that has been adapted to comics for so many times, by many comic artists. R.A. Kosasih, was one that was known for his mastery in creatingWayang Comics, and Mahabharata was his best creation. He created two versions of Mahabharata comics. The first was in 1955, published by Melodi and the second in 1975, by Maranatha. The storylines were basically the same, but there were differences not only in formats or spelling system, but in the visual narratives. The pictures in Maranatha version were designed in a more up dated style in comics. In the Maranatha version, R.A. Kosasih adjusted his drawing style like younger artist at that time. The angles of the scene drawn were more dynamic and variated. The scene itself expressed an adjustment to the lifestyles at that time. Consciously or unconsciously, R.A. Kosasih practised what a popular artist usually did: to always adapt to changes of. Even in his 56th of age he still succeeded to create another popular work.